PENGARUH CASA, NPL, DAN VARIABEL MAKROEKONOMI TERHADAP KREDIT YANG DIBERIKAN BANK UMUM DI INDONESIA ( Studi Kasus Bank Buku IV di Indonesia ) - Yulianto Yulianto; Meina Wulansari Yusniar (Universitas Lambung Mangkurat, 2021)
Banking has a strategic role in promoting economic growth, one of which is through financing or credit to the public and productive sectors. There are factors that influence the main activities of banks to channel credit to the public, namely factors from internal and external banks. The purpose of this study was to examine the effect of CASA, NPL, SBI interest rates and GDP on loans granted by commercial banks in Indonesia. This research is a causality study to determine the relationship and influence between two or more variables. The population of this study is all conventional banks listed on the Indonesia Stock Exchange. Banks that have the variables needed in the study with a sample of 8 banks obtained by purposive sampling method and the research time span is 4 years in 2016 - 2019. The research hypothesis is tested using multiple linear regression with the SPSS v25 program. The results of the T test show that CASA has a positive and significant effect on the amount of lending, while NPL, SBI interest rates and GDP have no effect on the amount of credit disbursed by commercial banks in Indonesia.